Capistrano de Abreu’s international scientific network - Christino, Beatriz (Revista do Instituto de Estudos Brasileiros, 2007)
A few Brazilian historians believed that Capistrano de Abreu wasted his time with his researches about South-American languages. In their opinion, there were almost nobody interested in that subject during the years 1890-1929. This article aims to refuse this idea by showing that Capistrano took part of the main international scientific communities and was considered an expert in that field.